Paleoceanography of northeastern Fram Strait since the last glacial maximum: Palynological evidence of large amplitude changes - Falardeau, Jade; De Vernal, Anne; Spielhagen, Robert F. (Quaternary Science Reviews, 2018)

Quaternary dinoflagellate cysts in the Arctic Ocean: Potential and limitations for stratigraphy and paleoenvironmental reconstructions - Matthiessen, Jens; Schreck, Michael; De Schepper, Stijn; Zorzi, Coralie; De Vernal, Anne (Quaternary Science Reviews, 2018)

Arctic environmental change beyond instrumental records: introduction and overview - Ó Cofaigh, Colm; Kirchner, Nina; Fedorov, Grigory; Noormets, Riko; De Vernal, Anne (arktos, 2018)

Identification key for Pliocene and Quaternary Spiniferites taxa bearing intergonal processes based on observations from estuarine and coastal environments - Limoges, Audrey; Londeix, Laurent; Mertens, Kenneth Neil; Rochon, André; Pospelova, Vera; Cuéllar, Tomasa; De Vernal, Anne (Palynology, 2018)

Late Holocene Sea Surface Instabilities in the Disko Bugt Area, West Greenland, in Phase With δ18 O Oscillations at Camp Century - Allan, Estelle; De Vernal, Anne; Knudsen, Mads Faurschou; Hillaire‐Marcel, Claude; Moros, Matthias; Ribeiro, Sofia; Ouellet‐Bernier, Marie‐Michèle; Seidenkrantz, Marit‐Solveig (Paleoceanography and Paleoclimatology, 2018)
Abstract Palynological analyses of sediment core MSM343310 from Disko Bugt (68°38′861°N, 53°49′493°W) document decadal‐ to centennial‐scale variability of sea surface conditions during the last ~ 3,600 years. Dinocyst fluxes (>10 4 cysts/cm 2 yr −1 ) indicate a very high productivity. Dinocyst assemblages dominated by Islandinium minutum , Brigantedinium spp., Islandinium ? cezare , and the cyst of Pentapharsodinium dalei suggest low surface salinity and marked shifts in summer sea surface temperature. The application of the modern analog technique to dinocyst assemblages, using an updated reference data set with new sites from the West Greenland margin, led to reconstruct decadal‐centennial‐scale variations in sea surface salinity and temperature, in phase with the δ 18 O variations in the Camp Century ice core. At ~ 1.5 ka BP, the seasonal sea ice cover records an important regime change, from winter‐only sea ice to more unstable conditions marked by successive cooling pulses with sea ice cover of up to 8 months/yr. The data suggest a close relationship between hydrographic conditions and regional climate over Greenland. Our record shows variations with a mean 200 years periodicity until ~2 ka BP, which supports the hypothesis of climate variations driven by solar variability. After 1.5 ka BP, our data show a variability characterized by a 60–70 year periodicity, which suggests linkages with the Atlantic Multidecadal Oscillation and southwestward migration of the atmospheric polar front. The most recent part of the record, from ~1900 CE to 2007 CE, is characterized by assemblages reflecting warmer surface conditions and reduced sea ice cover. , Key Points Sea surface salinity changes are used as indicators of fresh‐meltwater events and sea ice cover as a diagnostic feature of regional climate Changing sea surface conditions from Disko Bugt are closely related with regional climate over Greenland A marked change in surface waters at about 1.5 ka BP corresponds to enhanced sea ice cover and the onset of unstable conditions

Environmental forcing on the flux of organic-walled dinoflagellate cysts in recent sediments from a subtropical lagoon in the Gulf of California - Cuellar-Martinez, Tomasa; Alonso-Rodríguez, Rosalba; Ruiz-Fernández, Ana Carolina; De Vernal, Anne; Morquecho, Lourdes; Limoges, Audrey; Henry, Maryse; Sanchez-Cabeza, Joan-Albert (Science of The Total Environment, 2018)

Distribution and (palaeo)ecological affinities of the main Spiniferites taxa in the mid-high latitudes of the Northern Hemisphere - De Vernal, Anne; Eynaud, Frédérique; Henry, Maryse; Limoges, Audrey; Londeix, Laurent; Matthiessen, Jens; Marret, Fabienne; Pospelova, Vera; Radi, Taoufik; Rochon, André; Van Nieuwenhove, Nicolas; Zaragosi, Sébastien (Palynology, 2018)

The dinoflagellate cyst genera Achomosphaera Evitt 1963 and Spiniferites Mantell 1850 in Pliocene to modern sediments: a summary of round table discussions - Mertens, Kenneth Neil; Van Nieuwenhove, Nicolas; Gurdebeke, Pieter R.; Aydin, Hilal; Bogus, Kara; Bringué, Manuel; Dale, Barrie; De Schepper, Stijn; De Vernal, Anne; Ellegaard, Marianne; Grothe, Arjen; Gu, Haifeng; et al. (Palynology, 2018)

Palaeoclimate constraints on the impact of 2 °C anthropogenic warming and beyond - Fischer, Hubertus; Meissner, Katrin J.; Mix, Alan C.; Abram, Nerilie J.; Austermann, Jacqueline; Brovkin, Victor; Capron, Emilie; Colombaroli, Daniele; Daniau, Anne-Laure; Dyez, Kelsey A.; Felis, Thomas; Finkelstein, Sarah A.; et al. (Nature Geoscience, 2018)